Emergency contraceptive pill awareness in Bangladesh: missed opportunities in antenatal care and family welfare assistant visits - Tasnim Ara; Shahnaj Sultana Sathi; Shafayatul Islam Shiblee; Sumaiya Nusrat Esha; Md Tazvir Amin; Md Mahabubur Rahman (Reproductive Health)
Abstract Background Despite high coverage of antenatal care (ANC) and family welfare assistant (FWA) visits, emergency contraceptive pill (ECP) awareness is critically low in Bangladesh. We aim to investigate the missed opportunities in generating ECP awareness through ANC and FWA visit programs; and assess the missed opportunities and sociodemographic discrimination in receiving family planning (FP) counseling during ANC. Methods We used data from the nationwide Bangladesh Demographic and Health Survey 2017–18. Sample includes 5012 reproductive-aged women who gave live birth in the last 3 years preceding the survey. We used mixed-effect multiple logistic regression considering women nested within clusters to conclude. Results Nationally, 79% of women who gave live birth in the last 3 years preceding the survey were unaware of ECP. The estimated missed opportunities in generating ECP awareness was 59.5% in ANC, 0.9% in FWA visits, and 12.3% in both ANC and FWA visits. While FWA visit was not associated with ECP awareness, receiving FP counseling during ANC was significantly associated. About 88.4% of women remained unexposed to FP counseling through ANC during their last pregnancy. Missed opportunities in FP counseling during ANC was 80.4% of which 72% points were from qualified providers. The odds of missed opportunities was not associated with provider type, rather significantly increased among women with low education, lower parity, and poor socioeconomic status. Conclusions This study highlights the fragile status of FP counseling during ANC and FWA visits in generating ECP awareness. A prominent provider bias is excluding women of the disadvantageous sociodemographic group from receiving FP counseling.